Desarrollo de habilidades sociales y asertividad en niños de la Institución Educativa Inicial N° 386 Bellavista Callarú 2025 - Cayetano Coello, Belly (2025)
The main objective of this research was to establish the relationship between the development of social skills and assertiveness in children from the Initial Educational Institution N° 386 Bellavista Callarú during the year 2025. A relational methodology was adopted, implementing a bivariate, field, and cross-sectional design, with a population and sample composed of 200 children. Data collection was carried out through observation techniques, using observation guides that were validated by experts in the field. The results indicate that the correlational analysis revealed a p value of .000, which is below the significance threshold of .05, thus confirming the existence of a significant association between the studied variables. Furthermore, the correlation coefficient of rho = .478 suggests a moderate relationship, implying that as students' social skills increase, there is also an improvement in their assertiveness capacity. In conclusion, a significant and positive relationship between the development of social skills and assertiveness in children from the Initial Educational Institution N° 386 Bellavista Callarú is evidenced. These findings highlight the importance of promoting the development of social skills in early education, as they are intrinsically related to improvements in assertiveness.